Triazine-Based Conjugated Microporous Polymers With Different Linkage Units for Visible Light–Driven Hydrogen Evolution - Sheng, Qiannan; Zhong, Xiujuan; Shang, Qianqian; Dong, YunYun; Zhao, Jinsheng; Du, Yuchang; Xie, Yu (Frontiers in Chemistry, 2022)
Conjugated microporous polymers (CMPs), as a kind of two-dimensional material, have attracted extensive attention due to their advantages in visible light–driven photocatalytic splitting of water for hydrogen evolution. However, improving the microstructure and electronic structure of the material to enhance their photocatalytic performance for hydrogen evolution remains a challenge. We designed and reported two analogous CMPs including CMP-1 and CMP-2 that contain triazine and dibenzothiophene-S,S-dioxide units, which were prepared by Pd-catalyzed Suzuki-Miyaura coupling reaction. The main difference of two CMPs is that the triazine units are connected to benzene unit (CMP-1) or thiophene unit (CMP-2). Both of the CMPs exhibit excellent light capture capability, and compared with CMP-2, CMP-1 has faster separation rates and lower recombination rates for the charge carriers (electron/hole), and then, a higher hydrogen evolution rate was obtained from water decomposition reaction. We find the H2 production rate of CMP-1 can be up to 9,698.53 μmol g−1h −1, which is about twice of that of CMP-2. This work suggests that molecular design is a potent method to optimize the photocatalytic performance toward hydrogen evolution of the CMPs.